Literary Discourse : A Semiotic-Pragmatic Approach to Literature - Johansen, Jorgen Dines (Book collections on Project MUSE., 2002)
At a moment when 'literature' threatens to be collapsed into other discourses, or to be subsumed by such terms as 'narrative' and 'genre, ' J°rgen Dines Johansen, although he recognizes its protean nature, focuses on literature itself as it relates to other discourses. Using the semiotic theory of the American philosopher Charles S. Peirce as the principal influence, Johansen applies, in a highly erudite fashion, psychoanalysis, psychology, literary hermeneutics, literary history, Habermasian communication, and discourse theory to literature, and, in the process, redefines it. The text is divided into three major sections: an introductory exposition of the Peircean sign concept and the concept of discourse; an extensive discussion of various apexes of the semiotic pyramid; and a semiotic analysis of the hermeneutic problems of interpreting literature based on the theoretical work of Peirce, Habermas, and Gadamer. Such an ambitious project provides scholars not only with a pragmatic, multi-functional definition of literature but also with a thorough examination of the applicability of theory as it relates to analytic procedures.